PLAYDOUGH TO REDUCE ANXIETY”: Alternative Therapy in Pre-School Children with Hospitality - naning puji suryantini; Asirotul Ma'rifah; Indra Yulianti; Rina Mardiyana; Ariu Dewi Yanti; Indah Kusmindarti (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2019)
Hospitalization is an experience that produces every child who has physical and psychological effects as a result of the environment, and officers they do not know. Therefore the effort that can be done by nurses is to provide distraction therapy with playdough. The study aimed to prove the effect of treatment on Playdough play on anxiety in preschoolers because of hospitalization in the Kertawijaya Room Dr. Wahidin Sudiro Husodo Mojokerto. The design of this study uses pre-experiment with one group pretest approach. The population in this study were all preschool children who were in hospital treatment in the first week of October 2018. Samples were 20 children, with consecutive sampling. Playdough therapy for 20 children. Data collection used a mYPAS (Modified Yale Preoperative Anxiety Scale) questionnaire. After that, the data processing with Wilcoxon signed test was 0.00 which was <0.05, As for the conclusions in this study there is a therapeutic effect of playing plasticine on children's anxiety with hospitalization. The value of preschool children's anxiety before being given play therapy is the majority of respondents 13 respondents (65%) experienced moderate anxiety and And a small proportion of respondents experienced severe anxiety as many as 5 respondents (25%). The value of anxiety after being given play therapy most of the respondents experienced a decrease in anxiety as many as 12 respondents (60%) experienced mild anxiety and almost half of the respondents were 8 respondents (40%). Stress will stimulate the body to send messages from the hypothalamus to the adrenal gland which will affect vasodilation and vasoconstriction of blood vessels that will determine the increase or decrease in blood pressure which is one of the physiological characteristics of the body when experiencing anxiety.